Analysis of Genetic Association Studies - Zheng, Gang; Yang, Yaning; Zhu, Xiaofeng; Elston, Robert C. (Statistics for Biology and Health,, 2012)
Analysis of Genetic Association Studies is both a graduate level textbook in statistical genetics and genetic epidemiology, and a reference book for the analysis of genetic association studies. Students, researchers, and professionals will find the topics introduced in Analysis of Genetic Association Studies particularly relevant.  The book is applicable to the study of statistics, biostatistics, genetics and genetic epidemiology.    In addition to providing derivations, the book uses real examples and simulations to illustrate step-by-step applications.  Introductory chapters on probability and genetic epidemiology terminology provide the reader with necessary background knowledge.  The organization of this work allows for both casual reference and close study. .